FILSAFAH KEHIDUPAN TRITANGTU SUNDA DALAM FILM EKSPERIMENTAL ADAT “GAME OVER DRAMA” - Wiki Riandi; Erik Muhammad Pauhrizi; Sandie Gunara (Universitas Pendidikan Ganesha, 2023)
Creating an art work is a creative process of thinking and emotion in a practical and intuitive performance. Personal coding of the author in the creation of experimental film often leads to new interpretations. The empirical experience of tradition underlies the idea of creating a notable work. Sundanese Tritangtu philosophy, a tradition of the Sundanese, contributes to the formation of sundanese's creativity in working and understanding life. In this study, an experimental film entitled